Engagement in Favorite Activity and Implications for Cognition, Mental Health, and Function in Persons Living With and Without Dementia. (February 2022) - Regier, Natalie G.; Parisi, Jeanine M.; Perrin, Nancy; Gitlin, Laura N.
Little is known about the impact of engagement in personally meaningful activities for older adults. Thus, this study examines the impact of engagement in one's favorite activity on cognitive, emotional, functional, and health-related outcomes in older adults with and without cognitive impairment. Data were obtained from 1, 397 persons living with dementia (PLWD) and 4, 719 cognitively healthy persons (CHP) who participated in wave 2 of the National Health and Aging Trends Study (NHATS). Sociodemographic characteristics were examined by cognitive status. A multivariate analysis of variance indicated that, for PLWD, engagement in favorite activity was associated with greater functional independence and decreased depression. For CHP, engagement in favorite activity was associated with greater functional independence, decreased depression and anxiety, and better performance on memory measures. Findings suggest that engagement in valued activities that are considered personally meaningful may have significant and distinct benefits for persons with and without dementia.